PENYIAPAN BAHAN AJAR BAHASA ARAB UNTUK PELAJARAN TAMBAHAN DALAM RANGKA MENINGKATKAN PENGEMBANGAN KETERAMPILAN BERBAHASA DI MA’HAD ALY NAMIRA LAMONGAN - Affandi, Ahmad; Junaedi, Junaedi (Jurnal Ilmiah Global Education, 2023)
Development of Arabic Language Learning books for additional lessons to improve language skills at Ma'had Aly Namira Lamongan. This thesis aims to prepare teaching materials to improve language skills in Arabic language learning activities at Ma'had Aly Namira. However, in this institution, the level of awareness students approach lessons differently, especially in Arabic; some are superior to others, some are average, and some need additional help outside of class. Research was carried out using a pre and post-test design. As for the research results, the preparation of additional books in Arabic language teaching at the Namira Higher Institute for additional studies was well-prepared by researchers because additional books went through a lot of design, arbitration, correction, modification, then field experience, and finally the final production, namely additional books. Additional books for developing four skills at Ma'had Aly Namira Lamongan are good because the student results after teaching the book are higher than before teaching them, and that is because the average student results in the pre-test are 67.8125%. In the post test, the percentage is 89.625%. Likewise, the number of "t counts" is greater than the number of "t tables", namely 9.156. Depending on the results obtained by students in the pre and post-tests, results (t-test), and questionnaire results, it was found that additional books were designed to develop four language skills at Namira Higher Institute. Lamongan is effective. This has a positive effect on the development of language skills.